Deteksi Dini Terhadap Penyakit Tumor Otak Menggunakan Citra Magnetik Resonance Imaging (MRI) dengan Pendekatan Deep Convolutional Neural Network - Muhamad Salman; Rudi Kurniawan; Bunga Intan; Budi Santoso (Jurnal Ilmiah Informatika, 2025)
This study aims to develop an early detection system for brain tumors using MRI images with a Deep Convolutional Neural Network (DCNN) based on the ResNet152V2 architecture. Rapid detection of brain tumors is crucial for improving recovery chances; however, manual processes often face challenges due to limitations in technology and medical expertise. Therefore, this research offers an automated solution for analyzing MRI images.The methods used include data collection from public datasets, image preprocessing, and training the DCNN model. The ResNet152V2 model was chosen for its ability to address the vanishing gradient problem and its effectiveness in feature extraction. The results show that the model achieved an accuracy of 92.38% in classifying four types of brain tumors: Meningioma, Glioma, Pituitary, and No Tumor. Evaluation using a confusion matrix and classification report indicates good performance. This research is expected to contribute to the early diagnosis of brain tumors and serve as a reference for future studies in the application of artificial intelligence in the medical field.